Layered double hydroxide nanosheets: towards ultrasensitive tumor microenvironment responsive synergistic therapy. Issue 7 (29th January 2020) - Yan, Liang; Wang, Yingjie; Hu, Tingting; Mei, Xuan; Zhao, Xiaojie; Bian, Yanyan; Jin, Lan; Liang, Ruizheng; Weng, Xisheng; Wei, Min
Abstract : A 2D ultrathin nanomaterial of layered double hydroxides loaded with chlorin e6 was designed, which could be used for ultrasensitive tumor microenvironment responsive synergistic therapy. Abstract : The tumor microenvironment (TME), which is characterised by high H2 O2 and glutathione (GSH) levels, low pH value and hypoxia, imposes crucial influences on tumor therapeutic outcomes. Rational design and preparation of nanomaterial systems that are responsive to the intrinsic properties of the TME open a promising avenue towards tumor-specific treatment. Herein, CoMn-layered double hydroxide (CoMn-LDH) nanosheets were synthesized via a bottom-up method followed by surface modification with a photosensitizer, chlorin e6 (Ce6), which exhibited TME-responsive imaging as well as photodynamic and chemodynamic synergistic therapy (PDT/CDT). Due to their ultralow bond energy and large adsorption energy, CoMn-LDH nanosheets show fast self-degradability in a GSH (10 mM) microenvironment, giving an excellent CDT activity in mildly acidic conditions (pH = 6.5), superior GSH removal ability (99.82%) and O2 production (35.37 μg L −1 s −1 ). Moreover, Ce6/CoMn-LDH nanosheets display satisfactory photoacoustic (PA) imaging and GSH-enhanced magnetic resonance imaging (MRI) with a 45.1-fold T 1 -enhancement. In addition, both in vitro and in vivo therapeutic tests based on Ce6/CoMn-LDH demonstrate a satisfactory anticancer activity with complete cancer cell apoptosis and dramatic tumor elimination. This work provides a new perspective for the design of multifunctional 2D nanosheets towards a fully promoted TME-responsive synergistic therapy, which holds great promise for future clinical diagnosis and treatment.